The influence of Financial Literacy on Personal Financial Management in millennials in Indonesia - Ismed Wijaya; Dwi Retno Mulyanti; Tri Endar Susianto; Anis Noviya; Rahmat Purnomo (Nomico, 2025)
This study explores the impact of Financial Literacy on Personal Financial Management among millennials in Indonesia. Using a quantitative approach, the research investigates the relationship between financial knowledge and the ability to manage personal finances effectively. The findings indicate that financial literacy significantly influences personal financial management, highlighting its critical role in shaping sound financial behaviors. Millennials with higher levels of financial literacy tend to demonstrate better budgeting, saving, and investment habits, reducing the likelihood of debt accumulation and promoting long-term financial stability. Conversely, a lack of financial knowledge often leads to poor financial decisions, such as excessive use of credit cards, inadequate savings, and limited understanding of investment opportunities. This study contributes to the growing body of literature by focusing on the millennial generation in Indonesia, providing practical implications for stakeholders such as policymakers, financial institutions, and educators to enhance financial literacy programs. Tailored financial education initiatives, both in formal education settings and through community outreach programs, are recommended to address the specific needs of this demographic. Future research is encouraged to expand the scope by incorporating additional variables, such as technological adoption in financial management and the influence of socio-economic backgrounds, and employing mixed-method approaches to gain deeper insights into the behavioral aspects of financial decision-making.